Does the Discourse on the Increase of Value Added Tax have any legitimacy? Utilitarian Point of View - Erawan, M. Aufar Saputra Pratama; Zaid, Zaid; Fauzi, Muhammad Oky (International Journal of Social Science and Business, 2021)
From a utilitarian point of view, this research aimed to examine and assess the fifth draft of the KUP law, which plans to increase tariffs and the imposition of VAT on goods and services that should be excluded. By conducting a prescriptive analysis using the normative method, the results of this study found that the VAT rate would be increased to 12% with a minimum of 5% and a maximum of 15%. And in general, this policy can violate the principles of utilitarianism because it tends to injure social welfare. However, if VAT is only set on certain goods and services that are more exclusive to subsidize goods and services consumed by the poor, it will gain legitimacy in utilitarianism.